Implementasi Kebijakan Parkir di Kawasan Wisata Religi Sunan Ampel - Dwi Vira Safitri; Ertien Rining Nawangsari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Sunan Ampel Religious Tourism Area is a major destination in Surabaya that attracts thousands of visitors each year, but the lack of adequate parking space leads to illegal parking, causing traffic congestion and disorder. This research focuses on the importance of efficient parking management as part of the transportation infrastructure in large cities like Surabaya, particularly in the Sunan Ampel Religious Tourism Area. Surabaya, as one of the largest metropolitan cities in Indonesia, faces significant problems related to traffic congestion due to the high volume of vehicles. This research aims to analyze the implementation of the policy in the Sunan Ampel Religious Tourism Area and identify the obstacles and its impact on the community. This research aims to evaluate the implementation of Surabaya City Regional Regulation Number 3 of 2018 concerning Parking Management, with a focus on compliance, function execution, and its impact. The research method used is descriptive qualitative, involving interviews with parking attendants, service users, and direct observation. Data were analyzed using the Miles and Huberman model, which consists of data collection, data reduction, data presentation, and conclusion drawing. Research findings indicate that although policies have been implemented, there are challenges in their execution, such as low compliance of parking attendants with standard operating procedures (SOP) and the continued occurrence of illegal levies. In conclusion, increased supervision and training for parking attendants are necessary to ensure that the policy is implemented in accordance with regulations and has a positive impact on the community.